2021
DOI: 10.3389/fpubh.2021.689809
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the Risk of Catastrophic Health Expenditure in China: A Multi-Dimensional Analysis of Vulnerable Groups

Abstract: Background: In moving toward universal health coverage in China, it is crucial to identify which populations should be prioritized for which interventions rather than blindly increasing welfare packages or capital investments. We identify the characteristics of vulnerable groups from multiple perspectives through estimating catastrophic health expenditure (CHE) and recommend intervention priorities.Methods: Data were from National Health Service Survey conducted in 2003, 2008, and 2013. According to the recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…Our study found that patients suffering from hypertension enrolled in URRBMI and NRCMS had a higher CHE risk, but other insurance schemes also did not protect patients from CHE. Due to the defects of a low financing level, low compensatory benefits level, and poor ability of cost-sharing [39], many studies have also found that people covered by NRCMS have a greater CHE risk [40][41][42]. Additionally, there is evidence that many NRCMS funds do not include outpatient fees, rehabilitation, or long-term care for the elderly [39], which can further explain why middle-aged and elderly patients suffering from hypertension covered by NRCMS had a high CHE risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found that patients suffering from hypertension enrolled in URRBMI and NRCMS had a higher CHE risk, but other insurance schemes also did not protect patients from CHE. Due to the defects of a low financing level, low compensatory benefits level, and poor ability of cost-sharing [39], many studies have also found that people covered by NRCMS have a greater CHE risk [40][41][42]. Additionally, there is evidence that many NRCMS funds do not include outpatient fees, rehabilitation, or long-term care for the elderly [39], which can further explain why middle-aged and elderly patients suffering from hypertension covered by NRCMS had a high CHE risk.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, for URRBMI, following the integration of URBMI and NRCMS, compared to inpatient services, outpatient insurance policies still covered very limited diseases and had lower reimbursement ratios in most areas [22]. Therefore, medical expenses related to hypertension and most chronic diseases suitable for outpatient treatment can only be reimbursed after the use of inpatient services; thus, these patients either paid high fees or sought hospitalization [22,41].…”
Section: Discussionmentioning
confidence: 99%
“…Using oncology treatment modalities is dependent on socioeconomic status and financial protection provided by the states (12). Cancer treatment costs have been one of the major determinants of CHE in many countries, with an upward trend in recent years (13). Although there has been progress toward universal health coverage for non-communicable diseases, including cancer, since the announcement of the sustainable development goals in 2015, there is still a need for financial protection, especially for high-cost anti-cancer drugs (14).…”
Section: Treatmentmentioning
confidence: 99%
“…Dialogue with peers and medical professionals can improve HSBs' quality and quantity and is particularly essential for older people. In communities, people engage in dialogue with others regarding their health conditions and may modify their HSBs based on others' suggestions [12,13]. In particular, older people change their HSBs based mainly on their relatives and family's dialogues and suggestions due to limited access to communication resources and interactions with others [9,14].…”
Section: Introductionmentioning
confidence: 99%